Family violence risk, migration status and 'vulnerability': hearing the voices of immigrant women. (31st October 2018) - Maher, JaneMaree; Segrave, Marie
Abstract : In this paper, we draw on accounts of family violence risk offered by women from culturally and linguistically diverse (CALD) communities living in Victoria Australia, and examine how women's migration and experiences of difference impact on the risks they face from family violence. Women in refugee and immigrant communities are often understood as experiencing additional barriers and vulnerabilities when they face family violence; implicitly creating a deficit model of vulnerability attached to women's intersectional marginalization particularly in terms of migration and service regimes. Yet when we focus on women's own accounts of risk and safety, we argue that the 'vulnerabilities' these women experience are in fact predominantly created by service and legislative regimes that operate in terms of gender and migration. Rather than assuming that such vulnerabilities are inherent for women from CALD communities, we need to better recognise women's own assessments of risk and their searches for safety. Service and legislative responses that can support rather than inhibit women's efforts to secure their own safety are critical.